2011
DOI: 10.1111/j.1365-2672.2011.05110.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of bismuth thiols against biofilms formed by bacteria isolated from human chronic wounds

Abstract: Aims:  The purpose of this study was to evaluate the antimicrobial efficacy of thirteen bismuth thiol preparations for bactericidal activity against established biofilms formed by two bacteria isolated from human chronic wounds. Methods:  Single species biofilms of a Pseudomonas aeruginosa or a methicillin‐resistant Staphylococcus aureus were grown in either colony biofilm or drip‐flow reactors systems. Biofilms were challenged with bismuth thiols, antibiotics or silver sulfadiazine, and log reductions were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Statistical analysis was performed using contingency tables analyzed with a Fisher exact test comparing the number of contaminated bone samples for each PUR þ D-AA treatment group to the PUR blank scaffold. highlighted the potential of bacterial signaling molecules that trigger biofilm dispersal, such as bismuth thiols [20,56], quorumsensing inhibitors and analogs [57], and D-AAs [26,27], as therapeutic agents for treatment of chronic infections. In this study, we have shown that local delivery of D-AAs from PUR scaffolds inhibits biofilm formation by clinical isolates of S. aureus both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis was performed using contingency tables analyzed with a Fisher exact test comparing the number of contaminated bone samples for each PUR þ D-AA treatment group to the PUR blank scaffold. highlighted the potential of bacterial signaling molecules that trigger biofilm dispersal, such as bismuth thiols [20,56], quorumsensing inhibitors and analogs [57], and D-AAs [26,27], as therapeutic agents for treatment of chronic infections. In this study, we have shown that local delivery of D-AAs from PUR scaffolds inhibits biofilm formation by clinical isolates of S. aureus both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the specificity and effectiveness of these molecules for dispersing biofilms, the use of biofilm dispersal agents has attracted considerable interest for the treatment of biofilm-associated infections [18,19]. Recent studies have shown that use of biofilm dispersal agents, including bismuth thiols [20], recombinant DNAses [21], and diffusible soluble factors [22,23], can disperse biofilms in vitro and improve healing of biofilm-associated infections in vivo [24,25]. However, toxicity to viable host tissues (as observed for bismuth thiols and xylitol), as well as the specificity of these agents for certain bacterial species and/or strains, may preclude their use as broad therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the case of CSA-13, a variety of compounds that have similar methods of action have emerged over the past decade or more and may be candidates for this initiative. These include squalamine (44), squalamine derivatives (45), naturally occurring antimicrobial peptides (46), and bismuth thiolbased compounds (47). In this and a previous study, CSA-13 has demonstrated the promising ability to elute from a coating and eradicate bacterial biofilms in proximity to a coated material.…”
mentioning
confidence: 77%
“…Although local delivery of antibiotics can achieve bactericidal concentrations, many clinically used antibiotics, including rifampin, doxycycline, and penicillin, are either cytotoxic or inhibit osteogenic differentiation in vitro at therapeutically relevant concentrations [39]. Alternatives to antibiotics include agents that have inhibitory and/or dispersive activity against biofilms such as bismuth thiols [17], recombinant DNAses [25], quorumsensing inhibitors [22], and D-AAs [3,26,41], which have been reported to disperse biofilms in vitro and improve healing of biofilm-associated infections in vivo [7,46]. DAAs are active against a broad spectrum of bacterial species, and local delivery of D-AAs from bone grafts has been shown to reduce the frequency of infection of open fractures contaminated with S aureus in vivo [41].…”
Section: Discussionmentioning
confidence: 99%